Method to Determine the Optimal Aptamer-to-Bead Ratio by Using Flow Cytometry - Sun Young Lee; Eun-Ok Kim; Daehyuk Jang; Soonjae Hwang; Ki-Jong Rhee; Miyong Yun (Scientifica)
Research on the effective attachment of aptamers to beads, which is essential for using aptamers, has made relatively little progress. Here, we demonstrate a new method based on flow cytometry to determine the optimal aptamer-to-bead ratio for aptamer immobilization. The fluorescence intensity increased with a gradual two-fold increase in the aptamer fluorescence concentration, peaked at an aptamer-to-bead ratio of 2.56 × 105, and tended to decrease at higher ratios. A similar pattern was observed in an additional analysis using fluorescence microscopy. However, measurement of the free aptamer concentration after the aptamer-bead conjugation reaction revealed a large aptamer loss compared to the 1.28 × 105 aptamer-bead ratio. In addition, the binding efficiency of the aptamer/bead to the target was highest at the aptamer-to-bead ratio of 1.28 × 105. Taken together, our data suggest that the proposed method is the best and easiest for determining the optimal aptamer-to-bead ratio.